Prerogatywy prymasa Polski - Janczewski, Zbigniew (Śląskie Studia Historyczno-Teologiczne, 1998)
Many years in the Roman catholic Church exists the title – „primate”. Primates of Poland are very important persons. From the sixteen century they had specially commanding rights on the polish Church and the state. Extraordinary prerogatives (from the popes) had three primates, cardinals Hlond, Wyszyński and Glemp during the domination of communists in the our country. The article tells about this questions.